2017
DOI: 10.1016/j.amjsurg.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene expression profiles are associated with a pathologic complete response to neoadjuvant therapy in esophageal adenocarcinoma

Abstract: EAC tumors that demonstrated a pCR have genetic profiles that are significantly different from typical NR profiles. The genes CCL28 and DKK3 are potential predictors of treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Biomarker studies to date have been hampered by small patient numbers and authors frequently cited the inadequate powering of their studies as a fundamental limitation [ 49 , 52 , 61 , 90 ]. Incorporating small sample sizes relative to the number of gene expression measurements means that gene expression studies are vulnerable to overfitting, often due to failure to correct for multiple hypothesis testing [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomarker studies to date have been hampered by small patient numbers and authors frequently cited the inadequate powering of their studies as a fundamental limitation [ 49 , 52 , 61 , 90 ]. Incorporating small sample sizes relative to the number of gene expression measurements means that gene expression studies are vulnerable to overfitting, often due to failure to correct for multiple hypothesis testing [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…McLaren et al . also used FFPE endoscopic biopsies to evaluate the expression of 11 genes using RT–PCR [ 49 ]. Most treatment regimens involved platinum agents and 5-FU, although exact regimens varied significantly and the majority of studies assessed pathological response but utilized a variety of classification systems and cut-offs.…”
Section: Predictive Biomarkers In Oesophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Gene CCL28 was overexpressed in pathologic complete response patients, and it could be a potential predictor of treatment response. 44 Lysyl oxidase-like 2 (LOXL2), a member of the lysyl oxidase family, plays an important role in the biosynthesis and tumor development of extracellular matrix protein; wild-type LOXL2 (LOXL2Δ72) significantly promotes esophageal squamous cells by upregulating CCL28 cancer ESCC cell migration. 45 …”
Section: Discussionmentioning
confidence: 99%
“…No association with miRNAs or promoter methylation status was found while treatment of MB cells with Trichostatin A (TSA), a potent inhibitor of histone deacetylases (HDAC), was able to restore both DKK3 mRNA and protein (Valdora et al, ). Recently, it was also reported that DKK3 expression can work as a predictor of response to chemotherapy with the genes CCL28 and DKK3 being potential predictors of treatment response to neoadjuvant chemotherapy in esophageal cancer (McLaren et al, ). Moreover, it was included in the seven‐gene expression signature that was demonstrated to be an accurate predictor of clinical outcome in patients with ovarian cancer (Wang, Wang, Zhou, Yu, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%